Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Sepatu Goox di JABODETABEK - Febri Paber Marulop; Ignatius Ario Sumbogo (STREAMING, 2022)
The purpose of this study was to determine and analyze the effect of product quality on purchasing decisions, to determine and analyze the effect of price on purchasing decisions and to determine and analyze the effect of product quality and price on purchasing decisions for goox shoes. The approach used in this study is an associative approach. The population in this study is the whole. while the sample that meets the criteria for sampling the observations made amounted to100 respondents. The data collection technique in this study used a questionnaire technique. The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, Hypothesis Testing (t-test and F-test), and the Coefficient of Determination. The data processing in this study used the SPSS (Statistical Package for the Social Sciences) software program version 24.00. Partially it is known that product quality has a positive and significant influence on purchasing decisions for goox shoes where it is obtained (tcount.6,692) > (ttabel 1,984) and sig 0.000 <0.05. Partially it is known that the price has a positive and significant influence on the decision to buy goox shoes where it is obtained (tcount.4.453) > (ttabel 1.984) and the sig. 0.000 <0.05. Simultaneously, it is known that product quality and price have a significant influence on the decision to buy goox shoes where it is obtained (Fcount.37.694) > (Ftabel 3.09) and sig 0.000 <0.05.